Insight into Molecular Interactions of Two Methyl Benzoate Derivatives with Bovine Serum Albumin - Karolina Baranowska (MDPI AG, 2021)
The nature and mechanisms of interaction between two selected methyl benzoate derivatives (methyl o-methoxy p-methylaminobenzoate–I and methyl o-hydroxy p-methylaminobenzoate–II) and model transport protein bovine serum albumin (BSA) was studied using steady-state and time-resolved spectroscopic techniques. In order to understand the role of Trp residue of BSA in the I-BSA and II-BSA interaction, the effect of free Trp amino acid on the both emission modes (LE–locally excited (I and II) and ESIPT–excited state intramolecular proton transfer (II)) was investigated as well. Experimental results show that the investigated interactions (with both BSA and Trp) are mostly conditioned by the ground and excited state complex formation processes. Both molecules form stable complexes with BSA and Trp (with 1:1 stoichiometry) in the ground and excited states. The binding constants were in the order of 104 M−1. The absorption- and fluorescence-titration experiments along with the time-resolved fluorescence measurements show that the binding of the I and II causes fluorescence quenching of BSA through the static mechanism, revealing a 1:1 interaction. The magnitude and the sign of the thermodynamic parameters, ΔH, ΔS, and ΔG, determined from van’t Hoff relationship, confirm the predominance of the hydrogen-bonding interactions for the binding phenomenon. To improve and complete knowledge of methyl benzoate derivative-protein interactions in relation to supramolecular solvation dynamics, the time-dependent fluorescence Stokes’ shifts, represented by the normalized spectral response function c(t), was studied. Our studies reveal that the solvation dynamics that occurs in subpicosecond time scale in neat solvents of different polarities is slowed down significantly when the organic molecule is transferred to BSA cavity.